Pengaruh Gaya Siklis Aksial-Torsial pada Model Simulasi Sambungan Pipa Apung Menurut Teori Gaya Dua Permukaan - Sahlan Sahlan (Universitas Muhammadiyah Yogyakarta, 2014)
The two-surface theory consists of a yield surface and a loading surface, in which the surface may be defined diffrerently (axial and torsional). A Simulation experimental study on the inelastic behavior of tubular annealed alluminum alloy Alumina Duroll tubular specimens subjected to combined axial and torsional stress cycles is presented. Particular attention is paid to the question of how plastic strain is developed and how the yield surface moves along the 90o out-of-phase stress cycle for simulation model of floating hose. Experimental result agree qualitatively with the prediction of the two surface plasticity theory. This Research is based on case study research pipeline buoyancy (floating hoses)